Selenium nanoparticle rapidly synthesized by a novel highly selenite-tolerant strain Proteus penneri LAB-1 - Mingshi Wang; Daihua Jiang; Xuejiao Huang (iScience, 2022)
Summary: Microorganisms with high selenite-tolerant and efficient reduction ability of selenite have seldom been reported. In this study, a highly selenite-resistant strain (up to 500 mM), isolated from lateritic red soil, was identified as Proteus penneri LAB-1. Remarkably, isolate LAB-1 reduced nearly 2 mM of selenite within 18 h with the production of selenium nanoparticles (SeNPs) at the beginning of the exponential phase. Moreover, in vitro selenite reduction activities of strain LAB-1 were detected in the membrane protein fraction with or without NADPH/NADH as electron donors. Strain LAB-1 transported selenite to the membrane via nitrate transport protein. The selenite was reduced to SeNPs through the glutathione pathway and the catalysis of nitrate reductase, and the glutathione pathway played the decisive role. P. penneri LAB-1 could be a potential candidate for the selenite bioremediation and SeNPs synthesis.